The case of the mummified pigs : and other mysteries in nature - Quinlan, Susan E.; Dewey, Jennifer (Honesdale, PA : Boyds Mills Press, 1995)
A description of scientific research that explains the reasons for phenomena in nature
Includes bibliographic references and index.
1000
Keywords: Nature -- Juvenile literature; Science -- Juvenile literature; Science -- Miscellanea